SnO2-вмісні каталізатори для перетворення моноцукрів на хімічні продукти з доданою вартістю - Prudius, Svitlana V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
The article is devoted to the review of scientific works on the use of SnO2-containing mixed oxides as catalysts for the conversion of monosaccharides into value-added chemical products. Fossil feedstocks such as oil, coal, and natural gas, once the dominant sources for fuels and petrochemicals, are being gradually replaced by biomass and waste-derived alternatives. In particular, the study highlights the potential of sugar-based biomass as key renewable feedstocks for the synthesis of high-value-added chemicals. A detailed review is provided on catalytic strategies for biomass conversion, with a focus on heterogeneous acid and bifunctional oxide catalysts containing tin ions. These catalysts demonstrate significant promise due to their thermal stability, reusability, and reduced environmental footprint compared to traditional homogeneous acid systems. The article explores the structural, acidic, and redox properties of tin-containing mixed oxides such as ZrO₂–SiO₂–SnO₂, SnO₂/Al₂O₃, ZnO–SnO₂/Al₂O₃, and CeO₂–SnO₂/Al₂O₃, obtained via sol–gel synthesis or impregnation techniques. Special emphasis is placed on the catalytic role of Lewis and Brønsted acid sites formed by Sn⁴⁺ ions in tetrahedral and octahedral coordination. These active sites enable a variety of key biomass-derived transformations, including dihydroxyacetone conversion to methyl lactate, and selective production of levulinic and formic acids, esters of lactic and glycolic acids from fructose and xylose. Experimental results show high selectivity and yields under mild conditions, confirming the industrial potential of such catalysts. For example, superacid ZrO₂–SiO₂–SnO₂ allow complete fructose conversion to levulinic and formic acids with high yields (at 80÷90 mol. %). The SnO2/Al2O3 catalyst (5 wt. % tin dioxide) in a flow regime converts dihydroxyacetone, the simplest monosaccharide, to methyl lactate (selectivity 90 mol. %). ZnO–SnO₂/Al₂O₃ catalyst with basic and acid centers promotes complete transformation of fructose to alkyl lactates (yields of ethyl and methyl lactates 56 % and 70 % respectively), while bifunctional CeO₂–SnO₂/Al₂O₃ catalyst enable direct transformation of xylose (100 % conversion) with yield of methyl lactate and methyl glycolate in 42 % and 24 % respectively. The multifunctional properties of Sn-containing mixed oxide catalysts - combining acidic, basic, and redox sites - open pathways for cascade reactions and integrated biomass valorization.